Spatial frameworks for robust estimation of yield gaps - Rattalino Edreira, Juan Ignacio (2021)
Fil: Rattalino Edreira, Juan Ignacio. University of Nebraska - Lincoln. Department of Agronomy and Horticulture. Lincoln, NE, USA.